RIP-Seq of EZH2 Identifies TCONS-00036665 as a Regulator of Myogenesis in Pigs - Wang, Shanshan; Xu, Xuewen; Liu, Yan; Jin, Jianjun; Zhu, Feng; Bai, Wei; Guo, Yubo; Zhang, Jiali; Zuo, Hao; Xu, Zaiyan; Zuo, Bo (Frontiers in Cell and Developmental Biology, 2021)
Enhancer of zeste homologue 2 (EZH2) is the catalytic subunit of polycomb repressive complex 2 and contains a SET domain that catalyzes histone H3 trimethylation on lysine 27 (H3K27me3) to generate an epigenetic silencing mark. EZH2 interacts with transcription factors or RNA transcripts to perform its function. In this study, we applied RNA immunoprecipitation sequencing and long intergenic non-coding RNA (lincRNA) sequencing methods to identify EZH2-binding lincRNAs. A total of 356 novel EZH2-binding lincRNAs were identified by bioinformatics analysis and an EZH2-binding lincRNA TCONS-00036665 was characterized. TCONS-00036665 promoted pig skeletal satellite cell proliferation but inhibited cell differentiation, and this function was conserved between pigs and mice. Further mechanistic studies indicated that TCONS-00036665 can bind to EZH2 and recruits EZH2 to the promoters of the target genes p21, MyoG, and Myh4, which leads to the enrichment of H3K27me3 and the repression of target gene expression and pig myogenesis. In conclusion, the lincRNA TCONS-00036665 regulates pig myogenesis through its interaction with EZH2.